2023
DOI: 10.3390/designs7040086
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Multifunctional Bio-Inspired Design Concept Generation through Case-Based Expandable Domain Integrated Design (xDID) Model

Abstract: Combining different features inspired by biological systems is necessary to obtain uncom-mon and unique multifunctional biologically inspired conceptual designs. The Expandable Domain Integrated Design (xDID) model is proposed to facilitate the multifunctional concept generation process. The xDID model extends the previously defined Domain Integrated Design (DID) method. The xDID model classifies biological features by their feature characteristics taken from various case-based bio-inspired design examples int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The directional hierarchical arrangement of nano-tips on microstructures [25] (Orientation) Wings when tilted downwards. [25] functions [14,16]. The framework comprises three steps namely,…”
Section: (Arrangement)mentioning
confidence: 99%
See 2 more Smart Citations
“…The directional hierarchical arrangement of nano-tips on microstructures [25] (Orientation) Wings when tilted downwards. [25] functions [14,16]. The framework comprises three steps namely,…”
Section: (Arrangement)mentioning
confidence: 99%
“…xDID supports the extension of Domains for classifying the biological features that are tough to be defined according to the current definitions in DID. A detailed explanation of the classification, mapping, representation, and the application of the xDID model is reported in our previous research [16]. Multiple case studies have also been carried out to validate the xDID model and they are reported in [17][18][19].…”
Section: (Arrangement)mentioning
confidence: 99%
See 1 more Smart Citation